Kajian Awal Pemanfaatan Limbah Abu Boiler Kelapa Sawit Sebagai Material Konstruksi Non-Struktural - Rezi Munizar (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Palm oil boiler ash waste is a by-product of biomass combustion in the palm oil industry, the amount of which continues to increase in line with the growth of the industry. To date, the utilization of boiler ash waste has been limited, with most of it simply being dumped, thus posing potential environmental problems. A study is needed to evaluate the potential use of palm oil boiler ash waste as a non-structural construction material. This study aims to conduct a preliminary study of the characteristics and feasibility of using palm oil boiler ash waste as a non-structural construction material. The research method used is an experimental method in the laboratory, beginning with testing the physical characteristics of boiler ash, followed by basic mechanical testing on non-structural materials that utilize boiler ash as a mixed material. The parameters analyzed include compressive strength and water absorption, which are compared with the applicable quality standards for non-structural materials. The preliminary results show that palm oil boiler ash waste has the potential to be used as a non-structural construction material, especially as a substitute or additive in the manufacture of building materials.